Mutu Simplisia Kulit Buah Nanas (Ananas comosus (L) Merr.) Hasil Pengeringan Oven dan Sinar Matahari - Yunitasari, Norainny; Djamaludin, Nur Farikhah Abya; Tiadeka, Pemta (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Pineapple is a tropical plant and can help cure several health disorders. In general, pineapple has active compounds, such as alkaloids, tannins, and flavonoids. The success of identifying the presence of the active compound cannot be separated from whether the sample preparation stage was good or not, one of which was the drying stage. This research aims to determine the length of the oven and sunlight drying process for making good simplicia and determine the results of organoleptic, microscopic, and water content tests. This type of research is experimental. The sample used was pineapple skin. The quality test of the simplicia uses organoleptic, microscopic, and water content tests. The study's results showed that oven drying at a temperature of 60⁰ was carried out for 1 day with a time of 10 hours and sunlight drying was carried out for 110 hours (22 days) with a time per day of 4-5 hours. The results of the organoleptic test showed that the simplicia from the oven drying method was dark brown and the sun drying method was light brown, in the form of fine powder, had a sour and bitter taste, and a distinctive aromatic odor. The microscopic test results showed the presence of parenchymal tissue, stone cells, needle-type calcium oxalate crystals, and vascular bundles. The results of the water content test from both drying methods did not meet the quality requirements of the simplicia, namely 14.2% oven and 15% sun drying.